2008
DOI: 10.1093/ageing/afn093
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and main factors associated with early unplanned hospital readmission among French medical inpatients aged 75 and over admitted through emergency units

Abstract: markers of frailty (poor overall condition, pressure sores, prior hospitalisation) or severe disability (for self-feeding) were the most important predictors of early readmission among elderly medical inpatients. Early identification could facilitate preventive strategies in risk group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
77
3
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 142 publications
(102 citation statements)
references
References 25 publications
9
77
3
13
Order By: Relevance
“…In the study of Laniece et al functional disability was relevant to explain the risk of early readmissions in a cohort of patients aged 75 and older [23]. However, in this study, functional disability as assessed by the Barthel index was not associated with readmission, in agreement with the findings of Alarcon et al, who showed that limited activities of daily living were only predictive of hospital mortality and prolonged stay [24].…”
Section: Discussionsupporting
confidence: 89%
“…In the study of Laniece et al functional disability was relevant to explain the risk of early readmissions in a cohort of patients aged 75 and older [23]. However, in this study, functional disability as assessed by the Barthel index was not associated with readmission, in agreement with the findings of Alarcon et al, who showed that limited activities of daily living were only predictive of hospital mortality and prolonged stay [24].…”
Section: Discussionsupporting
confidence: 89%
“…We did not capture readmissions to outside hospitals, which account for 22% to 24% of all readmissions in prior studies, and therefore have underestimated the readmission rate in our population. 2,8 However, by limiting our data to 2 hospitals within 1 institution, we were able to include more detailed patient level data, which is not accurately available in other large databases. Also, while studies of risk factors in a managed care population (such as within Medicare, the Veterans Affairs medical centers, or countries with national integrated medical records) are able to capture all readmissions, this study is the first to evaluate readmissions risk factors in a truly heterogeneous U.S. inpatient medicine population without limitation by age or payer status.…”
Section: Discussionmentioning
confidence: 99%
“…A few clinical risk factors (such as age, number of prior admissions, and comorbidities) have been well defined in subgroups of general medicine inpatients. [6][7][8][9][10][11][12] Likewise, interventions aiming to reduce readmissions have also focused on subgroups, excluding a large portion of hospitalized patients (for example, non-English speakers and younger patients). [13][14][15][16][17][18][19][20] Other data have been derived in veterans or within non-US populations that have inherently different payer, race, ethnicity, and primary language composition, and may not be applicable outside those settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early identification of those at risk may be required facilitate intervention to prevent repeat hospitalisations. 15 Another identified an 8% readmission rate within three months for patients who received full community support at the time of discharge. On subsequent readmissions, over half could be discharged home again with the remaining likely to die in hospital or require institutional long-term care.…”
Section: Conflicts Of Interest Statementmentioning
confidence: 99%